الأنسنة وأثرها في الدراسات الحداثية للقرآن الكريم - نمسي, عبد السلام; شويخ, سعدية; حشيفة, وفاء (University of Eloued-جامعة الوادي, 2022)
" تناولت هذه الدراسة التي عنوناها بالأنسنة وأثرها في الدراسات الحداثية للقرآن الكريم ، موضوع الأنسنة الذي يعتبر الإنسان هو محوره ، باعتباره العنصر الوحيد القادر على إيجاد المعرفة بعيدا عن قيود النصوص الدينية التي تعتبر عند أصحاب هذا الإتجاه غير قادرة على الوصول إلى الحقيقة كما تطرقت الدراسة أيضا إلى موضوع نشأة الأنسنة ، وأصلها وكذلك أثرها في الدراسات القرآنية الحداثية . كما عرجت هذه الدراسة في جانبها التطبيقي على تصور الأنسنة من وجهة نظر المفكر والكاتب الجزائري محمد أركون ومدى تطابقها مع التعاليم الدينية الإسلامية . كما توجهت الدراسة إلى تصور الأنسية من وجهة نظر المفكر والكاتب المصري نصر حامد أبو زيد ، وقراءته لما جاءت به النزعة الأنسنية ومحاولة تطبيقها على ما جاءت به التعاليم الدينية الإسلامية . وتطرقت هذه الدراسة أيضا في الجانب التطبيقي منها إلى تصور الأنسنة من وجهة نظر الكاتب والمفكر المصري محمد شحرور الذي سعى إلى إبراز مدى تطابق النص الديني مع النزعة الأنسنية . وقد خلصت الدراسة في الأخير إلى مجموعة من النتائج التي وضحت تعريفها نشأة الأنسنة ومصادرها الأولى وتوصل الكتاب و المفكرين الذين تناولت الدراسة آراءهم هذه إلى النص الديني الإسلامي غير متطابق مع الأنسنة في كثير من القضايا والمسائل الاجتماعية ."" This study deal with the subject of Humanism, which considers the human being as the centerpiece, as he is the only being capable of finding knowledge away from the restrictions of holy scripts, which, according to the founders of this trend, is unable to finding out the truth. The study also explore the issue of the emergence of Humanism, its origin, and its impact on modern Quranic studies. In its practical aspect, this study also referred to the conception of Humanism from the point view of the Algerian thinker and writer Mohmmed Arkoun and the extent of its conformity with Islamic religious teachings. The study also aimed to visualize Humanism from the point view of the Egyptian thinker and writer Nasr Hamid Abu Zayd, and his reading of what the Humanism tend brought and an attempt to apply it on what was brought by Islamic religious teachings. In the practical aspect, this study also deal with the idea of visualizing Humanism from the point view of the Egyptian writer and thinker, Muhammad Shahrour, who tried to highlight the extent to which the holy scripts may correspond with the Humanism trend. Finally, the study concluded with a set of results that clarified its definition of the genesis of Humanism and its first sources, the writers and thinkers whose views were discussed in this study reached out that the Islamic holy scripts is not compatible with Humanism in many issues and social concerns."
مذكرة ماستر
Keywords: الأنسة - نشأة وأصل الأنسة – أثر الأنسنة – محمد أركون – نصر حامد أبو زيد – محمد شحرور; Humanism - Origin and genesis of Humanism - The Impact of Humanism - Mohammed Arkoun - Nasr Hamid Abu Zayd - Muhammad Shahrour